Antagonistic properties of preparation to themicromycetes Fusarium oxysporum Schltdl - I. Beznosko; T. Gorgan; I. Mosiychuk (Карантин і захист рослин)
Goal. To determine the antagonistic properties of the preparations MycoHelp, FitoHelp, Trichodermin-bio and Haupsin to the micromycetes Fusarium oxysporum Schltdl.